Transition metal oxide catalysts for exhaust gas oxidation - Wang,Ting (Nanyang Technological University, 2020)
Driven by the growing concern over air contamination, particularly the emission of exhaust gas, the development of air purification technologies is of paramount importance for maintaining a clean global environment. Heterogeneous catalysis as one of the most efficient responses to this pursuit has drawn a great deal of attention. While noble metal catalysts are an effective solution, their high cost and scarcity render them unsuitable to fulfill the growing demand. Attention has thus shifted to the more abundant transition metal oxides, with an expectation of designing highly effective catalysts. The rational design of efficient catalysts can be guided by gaining fundamental understandings on the structure-performance relationship, as well as identifying pertinent descriptors which can rationalize and predict the catalytic behaviors. Among the various earth-abundant oxide materials, cobalt-based spinel oxides or perovskite oxides have emerged as promising candidates, and thus in this thesis, specific attention has been given to those cobalt-based spinel oxide and perovskite oxide families. Two basic and major exhaust gas, i.e. CO and methane are employed. This dissertation first identifies the parameters that influence the activity of Co-Mn containing spinel oxide catalysts on CO oxidation. By tuning the ratio of octahedrally occupied Mn to Co in series of ZnMnxCo2−xO4 (x=0~2.0) spinel oxides, a correlation between the catalytic CO oxidation activity and eg occupancy of Mn cations or the O p-band center relative to the Fermi level has been established. These two indices of how the electronic structure influences the oxygen addition- and removal-related processes, are proposed to be the activity descriptors. Second, the underlying origin of the structure and temperature-dependent complete methane oxidation over Co-Ni containing spinel oxides is examined. Ni is introduced to substitute the octahedrally coordinated Co in series of ZnNixCo2−xO4 (x=0~0.8) for a tunable variation in electronic structure. Given a fair comparison of the catalyst intrinsic specific activity, it is found that the interplay between O p-band center and Moct d-band center is correlated with not only the methane oxidation activity but also the thermal stability and reaction mechanism of the catalysts. CH4-TPD-MS and O2-TPD tests further confirmed the DFT results with featured involvement of adsorbed oxygen or lattice oxygen. It is according proposed that the relative position between O p-band center and Moct d-band center can serve as an activity/mechanism descriptor of the methane complete oxidation for spinel oxides. Third, efforts are devoted to unveiling the applicability of the as-establish activity descriptor to perovskite oxides family. The structure-activity relationship of B-site substituted LaFexCo1-xO3 (x=0~1.0) perovskite oxides for complete methane oxidation is firstly investigated. It is revealed that the interplay between O p-band center and B site metal cation d-band center governs the catalytic comportment. The as-revealed governing role is further extended to the A-site substituted La1-xSrxCoO3 perovskite oxides for catalytic performance prediction, which turns out to be effective. Briefly, the interplay between O p-band center and B-site metal cation d-band center can specify the catalysts’ intrinsic property accountable for the catalytic performances and in turn predict the catalytic behavior.